ĐẶC ĐIỂM LÂM SÀNG VÀ HIỆU QUẢ ĐIỀU TRỊ CỦA LIỆU PHÁP OXY CAO ÁP Ở BỆNH NHÂN CHÓNG MẶT NGOẠI BIÊN - Trần, Thị Hằng; Nguyễn, Phương Nam; Phạm, Thị Duyên (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
CLINICAL CHARACTERISTICS AND THERAPEUTIC EFFECT OF HYPERBARIC OXYGEN THERAPY IN PATIENTS WITH PERIPHERAL VERTIGO This paper presents “Clinical characteristics and therapeutic efficacy of hyperbaric oxygen therapy in patients with peripheral vertigo” to determine the clinical features of peripheral vertigo and its therapeutic efficacy. The study was carried out at Hyperbaric Oxygen Center (Southern Branch of Joint Vietnam-Russia Tropical Science and Technology Research Center) from October 2021 to December 2022, with 60 patients, divided into 2 groups. Group 1 consisted of 30 patients was treated with hyperbaric oxygen therapy (HBOT) and group 2 consisted of 30 patients was treated with HBOT and drugs (vestibular inhibitors, antiemetics and brain tonics). The results showed that: vertigo often occured when changing head position, vertigo accompanied by nausea, loss of balance. After the treatment, the group treated with HBOT and drugs, the patient’s condition improved better, the level gradually increased with HBOT. In the group treated with HBOT and drugs, the mean score before treatment was 12.5 points, after 10 days of treatment was 4.37 points, after 20 days of treatment decreased to 0.63 points and after 30 days of treatment to 0.27 points. Particularly, in the group treated with HBOT, this rate was 12.33 points, respectively; 6.37 points; 2.1 points and 0.97 points (p < 0.05).